Edukasi Peningkatan Partisipasi Masyarakat Dalam Pengembangan Desa Wisata Pasca Pandemi Covid-19 di Desa Cikolelet Kabupaten Serang - Rahmawati, Rahmawati; Ilhan S, Afiatta; Imron, Imron (Komunitas : Jurnal Pengabdian Kepada Masyarakat, 2024)
Community participation in the development of tourism villages is the main thing. The community-based tourism approach strongly emphasizes the active involvement of the tourism village community. However, since the Covid-19 pandemic there has been a decline in the number of tourists and the impact on the decline in "enthusiasm" and community participation in the development of tourist villages. Likewise, the participation of the Cikolelet tourism village community has decreased the enthusiasm to contribute to the development of the tourism village. This activity aims to educate the community to increase their understanding of the forms of participation so that it has an impact on increasing their enthusiasm and involvement/contribution in the development of tourist villages. Forms of community participation consist of participation of ideas, energy, property and participation of skills. The training participants were Cikolelet villagers, pokdarwis members and representatives of MSME (UMKM). The results of the activity showed an increase in the community's understanding of tourism village development and the forms of participation that can be done. Recommendations for the results of the activity include the need for training in digitizing MSME marketing and preparing new pamphlets containing the latest tourist attractions.